Seminal Studies in Linguistics and Translation. - El-Zawawy, Amr M. (Cambridge Scholars Publishing, 2022)
This collection presents insights into the latest developments in linguistics and translation studies. It addresses many salient issues in both fields with considerable depth and lucidity, allowing fresh views to underpin, and even challenge, existing ideas. The contributors here are all distinguished scholars with extensive experience in the fields.